Romantic Diversitarianism: Problems and Promises. Issue 3 (3rd May 2020) - Chander, Manu Samriti
ABSTRACT: This paper responds to a question posed by the organizers of the 2019 meeting of the North American Society for the Study of Romanticism: how might A. O. Lovejoy's 1941 essay "The Meaning of Romanticism for the Historian of Ideas" have something new to say now, especially in relation to our current institutional circumstances as Romanticists? I focus on Lovejoy's treatment of Romantic Eigentümlichkeit, or "diversitarianism, " as a contributing factor in the rise of twentieth-century fascist movements. Pairing Lovejoy's essay with Rey Chow's "The Fascist Longings in Our Midst, " I suggest that Romantic-era diversitarianism already exhibited forms of desire that characterize fascism. By way of conclusion, I warn that a fascism at the heart of liberal multiculturalism threatens uncritical efforts to diversify Romanticism.